2012
DOI: 10.1364/josaa.29.001105
|View full text |Cite
|
Sign up to set email alerts
|

Overall gloss evaluation in the presence of multiple cues to surface glossiness

Abstract: Human observers use the information offered by various visual cues when evaluating the glossiness of a surface. Several studies have demonstrated the effect of each single cue to glossiness, but little has been reported on how multiple cues are integrated for the perception of surface gloss. This paper reports on a psychophysical study with real stimuli that are different regarding multiple visual gloss criteria. Four samples were presented to 15 observers under different conditions of illumination in a light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…In the present study, however, the shapes of these curves are quite heterogeneous and in most of the cases the curves are far from regaining their initial level. A closer look at the individual data sets of our present matching experiment suggests that there are at least two groups of subjects who show clear differences in their data trends (compare this with the findings from Leloup, Pointer, Dutré, & Hanselaer, 2012 , and those from Hansmann-Roth, Pont, & Mamassian, 2017 , who could also identify two different response groups among the subjects in their studies on gloss perception): Two of the seven subjects produced data curves that are in good agreement with those from our former study—and this is true for almost all shape and test smoothness conditions (see the black solid curves in Figure B1 in Appendix B; except for the “bunny” condition under the lowest test smoothness level, all curves show the characteristic U-shape). In contrast, the curves of the other five subjects generally lack an increase at higher light spread values (see the black dashed curves in Figure B1 in Appendix B), where the exact shape of the curve also seems to depend on the test object’s shape: Under the shape conditions “blob#1” and “bunny,” the curves can be described as strictly decreasing functions of the light spread, while under the shapes “blob#2” and “statue,” the mean smoothness settings rather seem to reach an asymptote at higher light spread levels.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the present study, however, the shapes of these curves are quite heterogeneous and in most of the cases the curves are far from regaining their initial level. A closer look at the individual data sets of our present matching experiment suggests that there are at least two groups of subjects who show clear differences in their data trends (compare this with the findings from Leloup, Pointer, Dutré, & Hanselaer, 2012 , and those from Hansmann-Roth, Pont, & Mamassian, 2017 , who could also identify two different response groups among the subjects in their studies on gloss perception): Two of the seven subjects produced data curves that are in good agreement with those from our former study—and this is true for almost all shape and test smoothness conditions (see the black solid curves in Figure B1 in Appendix B; except for the “bunny” condition under the lowest test smoothness level, all curves show the characteristic U-shape). In contrast, the curves of the other five subjects generally lack an increase at higher light spread values (see the black dashed curves in Figure B1 in Appendix B), where the exact shape of the curve also seems to depend on the test object’s shape: Under the shape conditions “blob#1” and “bunny,” the curves can be described as strictly decreasing functions of the light spread, while under the shapes “blob#2” and “statue,” the mean smoothness settings rather seem to reach an asymptote at higher light spread levels.…”
Section: Discussionsupporting
confidence: 67%
“…These individual preferences in turn may be due to the use of different weights for the set of image cues on which the glossiness estimate is based. In the field of gloss perception, it has repeatedly been found that different sources of information are taken differently into account by different observers ( Leloup et al., 2012 ; Phillips, Ferwerda, & Nunziata, 2010 ; Wendt et al., 2010 ; see also Chadwick & Kentridge, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, specular highlights inform the geometry of the folded fabric sample, hence indirectly affecting its display of mechanical properties, such as stiffness. The effects of color on perception of surface gloss has been discussed in several articles, but systematic research is needed (Chadwick & Kentridge, 2015;Hanada, 2012;Leloup, Pointer, Dutré, & Hanselaer, 2012;Nishida, Motoyoshi, & Maruya, 2011).…”
Section: Effect Of Colormentioning
confidence: 99%
“…Although specular glossmeters have been used in industry for decades and are still in use today, their limited capabilities have been recognized for a long time. The most important drawback is that the reported measurement results do not well correspond to the visual appraisal of surface gloss [6][7][8][9].…”
Section: Optical Characterization Of Surface Glossmentioning
confidence: 94%